Computer-based interactive tutorial versus traditional lecture for teaching introductory aspects of pain - Mark I. Johnson; David G. Dewhurst; Alan D. William (Association for Learning Technology, 1997)
Pain is one of the most frequent complaints presenting to medical institutions. However, pain and its management continues to be marginalized in the content of health-care professional education due in part to the multi-disciplinary nature of the subject which makes it difficult to locate within the curriculum (Bonica, 1987; Liebeskind and Melzack, 1987; Marcer and Deighton, 1988; Pilowsky, 1988). Furthermore, the factual elements relating to pain often overlap with other parts of the curriculum, making it impossible to decide who should deliver the information, and how much time can be devoted within the limited time frame of normal health-care professional courses (Max, 1992). The International Association for the Study of Pain (IASP) core curriculum on pain education was developed to overcome some of these problems (Fields, 1995).